The Use of Skim Milk and Essential Fatty Acids as an Alternative Method on Improving Yoghurt Nutrition Quality - Astuti, TY; Setyawardani, T (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The objective of the research was to investigate the effects of addition of different levels lemuru seafish oil on skim milk-based yoghurt in order to produce good quality and marketable yoghurt. The experiment consisted of lemuru seafish oil fractination based on its freesing point and the addition of extracted lemuru seafish oil to skim milk-based yoghurt at 0.50%; 1%; 1.50%; 2%. Yoghurt with 0% lemuru seafish oil was included as a control. A Completely Randomised Design was employed and each treatment has 5 replicates. Results showed that: (a) the addition of lemuru seafish oil up to 2% affected lactic acid contents of yoghurt but still within the normal range, (b) consumers preferred the smell and taste of yoghurt with 2% lemuru seafish oil; but they preferred the texture of yoghurt with 0.50% lemuru seafish oil, (c) the addition of lemuru seafish oil to skim milk-based yoghurt increased the nutritional quality of the products, especially the amount of omega 3 and omega 6 fatty acids. In order to get an ideal ratio between omega 3 and omega 6 fatty acids (4:1), it was recommended to further investigate the use of lemuru seafish oil on milk products and the addition of omega 3 fatty acids from different sources as well as the shelf life of yoghurt with added lemuru seafish oil. (Animal Production 8(1): 16-21 (2006) Key Words : Yoghurt, lemuru seafish oil, essential fatty acids